2014
DOI: 10.1016/j.drugalcdep.2014.08.013
|View full text |Cite
|
Sign up to set email alerts
|

Pain is associated with risky drinking over time among HIV-infected persons in St. Petersburg, Russia

Abstract: Background Pain is highly prevalent among persons with HIV. Alcohol may be used to “self-medicate” pain. This study examined the association between pain and risky alcohol use over time in a cohort of HIV-infected Russian drinkers. Methods This secondary analysis utilized longitudinal data from a randomized trial of a behavioral intervention. Subjects included HIV-infected adults who reported past 6-month risky drinking and unprotected sex and were recruited from HIV and addiction treatment sites in St. Pete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 61 publications
1
13
0
Order By: Relevance
“…In a previous study of HIV-infected persons in St. Petersburg we demonstrated that individuals with pain were more likely to report current use of illicit drugs, with the association being strongest for heroin use [24], and similar results have since been reported among HIV-infected injection drug users in the U.S. [25]. In a subsequent study, we demonstrated associations between pain and heavy drinking in the same cohort [26]. Alcohol and drugs can lower inhibitions that may lead to both high risk sex and drug risk behaviors.…”
Section: Introductionsupporting
confidence: 60%
See 1 more Smart Citation
“…In a previous study of HIV-infected persons in St. Petersburg we demonstrated that individuals with pain were more likely to report current use of illicit drugs, with the association being strongest for heroin use [24], and similar results have since been reported among HIV-infected injection drug users in the U.S. [25]. In a subsequent study, we demonstrated associations between pain and heavy drinking in the same cohort [26]. Alcohol and drugs can lower inhibitions that may lead to both high risk sex and drug risk behaviors.…”
Section: Introductionsupporting
confidence: 60%
“…In a prior study of symptoms among HIV-infected persons in the UK, it was observed that psychological, but not physical symptoms, were associated with increased risk of unprotected sex [39]. Previously, we demonstrated that individuals with pain were more likely to use illicit drugs (particularly heroin) and alcohol over time [24, 26]. This study adds to the current literature linking pain to substance use, demonstrating that pain is associated with use of alcohol prior to or during sex.…”
Section: Discussionmentioning
confidence: 99%
“… 28 , 104 Five studies (4 from South Africa and 1 from the United States) recruited women exclusively 79 , 92 or predominantly (proportion of women ranging from 72% to 88%). 88 , 121 , 122 The mean age ranged from 30.1 (SD = 5.2) 114 , 115 to 51.0 (SD = 9.3) years. 119 HIV duration was not consistently reported; however, of the studies providing data, duration ranged from 2.09 (SD = 1.22) 102 to 16.95 years (SD = 8.70).…”
Section: Resultsmentioning
confidence: 99%
“…For instance, pain is common and associated with unhealthy alcohol use among PLWH (Merlin, ; Merlin et al., ; Tsui et al., ). Because pain itself may interrupt engagement in HIV care (Berg et al., ; Merlin et al., ) and may also induce alcohol use as a coping mechanism (Tsui et al., ), alcohol's role in pain management among PLWH, is an area ripe for further study. Another issue in need of further investigation is alcohol's role in neuropathy among PLWH.…”
Section: Neurological Disordersmentioning
confidence: 99%